Intramural Hematoma of the Esophagus Complicating Severe Preeclampsia - Simone Garzon; Giovanni Zanconato; Nicoletta Zatti; Giuseppe Chiarioni; Massimo Franchi (Hindawi Limited, 2017)
Intramural hematoma of the esophagus is a rare injury causing esophageal mucosal dissection. Forceful vomiting and coagulopathy are common underlying causes in the elderly population taking antiplatelets or anticoagulation agents. Acute retrosternal pain followed by hematemesis and dysphagia differentiates the hematoma from other cardiac or thoracic emergencies, including acute myocardial infarction or aortic dissection. Direct inspection by endoscopy is useful, but chest computed tomography best assesses the degree of obliteration of the lumen and excludes other differential diagnoses. Intramural hematoma of the esophagus is generally benign and most patients recover fully with conservative treatment. Bleeding can be managed medically unless in hemodynamically unstable patients, for whom surgical or angiographic treatment may be attempted; only rarely esophageal obstruction requires endoscopic decompression. We report an unusual case of esophageal hematoma, presenting in a young preeclamptic woman after surgical delivery of a preterm twin pregnancy, with a favorable outcome following medical management.